African music in the Methodist Church of Southern Africa : a case study in the Western Cape - Stephenson, Mark H (Department of Religious Studies, 2015)
This study is an appraisal of African Music within the Methodist Church of Southern Africa with particular reference to the Western Cape. I develop and amplify a pilot study 4 in order to provide a model for further research into African Music in the Methodist Church of Southern Africa. The subject has a certain topical relevance. Many Churches are not only producing new hymn books but are also experimenting with new ways of communicating the gospel through music. 5 More recently, the Africanisation committee of the C.U.C. (Church Unity Commission) directed by its convenor the Rev. E. Baartman (President Elect of the Methodist Church of Southern Africa) recommended that the C.U.C. co-ordinate research into "Black theology, African liturgy and furthermore, at the Fifth Annual Symposium on Ethnomusicology, 30 August 1984 - 1 September 1984, Alain Barker reported that "while all agreed that the international perspective the Conference provided was of great value, serious debate on how the subject should be dealt with in this country was limited to a brief discussion at the end" . Some critics felt more practical involvement in African Music should have been a part of the Conference. In other words an academic assessment needs to be grounded in practice. (a) My purpose is to determine the meaning of African Music in the Methodist Church of Southern Africa, and to show that African Music is a contact point between Church and Culture, facilitating cultural liberation. (b)I have erected a framework to order the results of my research. It may be claimed that the method of approach is in many ways novel. Field work, recording and documentation on African Music in the Methodist Church of Southern Africa has to my knowledge never been published. This research is an attempt to make a start. We need to listen to Africa. As a fourth generation Methodist Minister, where else could I begin other than in the Methodist Church? As can be expected in an exploratory study, these findings point to areas which need more investigation. African Music articulates the most viable approach to respond to both the demands of the Gospel and African Culture. The aim of this study is to promote and teach people an appreciation of African Music within the broader context of the Church. (c) In the light of this, I have attempted four things: (i) African Music in the Methodist Church of Southern Africa is located in its broader African context by an examination of the roots of the Church within the Protestant tradition. (ii) Oral evidence was collected as a basis for critical reflection. (iii) A critical reflection is undertaken on some of the issues implicit in the words and music. (iv) An attempt is made to suggest ways and means of developing African Music within the life of the Church.